Policy responses to real world challenges associated with NEET youth: a scoping review - Paabort, Heidi; Flynn, Paul; Beilmann, Mai; Petrescu, Claudia (Frontiers in Sustainable Cities, 2023)
In the last decades, young people not in education or employment have become the focus of policy-makers worldwide, and there are high political expectations for various intervention initiatives. Despite the global focus, there is currently a lack of systemic knowledge of the factors supporting policy-making. Therefore, using scoping review methodology, a systematic literature overview of research findings in 2013–2021 on young people not in education or employment will be provided. The research revealed five categories to consider from a policy-making perspective: ‘NEET’ as a concept, the heterogeneity of the target group, the impact of policies for young people, possible interventions, and factors influencing young people’s coping strategies. Based on analysis, the target group requires applying the holistic principle where the young person is a unique person whose involvement in service creation supports the service’s compliance with the actual needs of young people. To support young people, it is important to consider differences within a single social group; the interaction between the different site-based policies; young people’s sense of self-perception and autonomy in entering support services; possible coping strategies and the need to provide support in a time and place-based flexible and caring environment through multidisciplinary teams. The study’s results support the importance of implementation and the identification of existing opportunities of the EU's reinforced Youth Guarantee guidelines and point to possible future research topics related to the target group.